On the primitive representations of finitely generated metabelian groups of finite rank over a field of non-zero characteristic - Tushev, A.V. (Carpathian Mathematical Publications, 2014)
We consider some conditions for imprimitivity of irreducible representations of a metebelian group G of finite rank over a field k. We shoved that in the case where char k = p > 0 these conditions strongly depend on existence of infinite p-sections in G.